Pengenalan Tenun Lurik Melalui Motion Comic “Nurika” di SD Negeri Mijipinilihan Surakarta - Yudi Wibowo; Zaidan Ramadan Ilyas; Andina Aulia Agustin (JURNAL PENGABDIAN TEKNOLOGI TEPAT GUNA, 2026)
Indonesia boasts a rich cultural heritage, notable for the lurik woven fabric that comes from Central Java and Yogyakarta. Nonetheless, the present generation of youth is beginning to value local cultural traditions because of the restricted access to engaging and pertinent educational resources, particularly in elementary education. At SDN Mijipinilihan, the teaching and learning process has yet to fully incorporate the understanding of lurik weaving culture. This challenge requires an inventive strategy that can effectively link children's experiences with local cultural principles. This community service endeavor aims to enhance students' comprehension and appreciation of local cultural heritage by developing digital learning materials inspired by motion comics. The project was executed as a motion comic named "Nurika," which explores the significance and philosophy of lurik fabric through an engaging visual storytelling approach. The approach involved socializing the program, providing teacher training, producing and screening media, facilitating class discussions, along with evaluation and mentoring. The results of this activity indicated a growth in students' comprehension of lurik weaving culture, as demonstrated by improved post-test scores in relation to pre-tests, along with enthusiastic student participation in discussions. Educators mentioned that this media assisted them in presenting cultural content in a more captivating and comprehensible manner for learners. In addition, this media was supplied to the school for continuous utilization. It can be inferred that using motion comics as an accessible medium grounded in local culture is an effective and pragmatic method for linking students to local wisdom principles. This program enhances students' cultural awareness while also improving teachers' skills in facilitating creative thematic education. Keywords: community engagement, comic creation, lurik fabric weaving, local traditions, educational resources, SDN Mijipinilihan